Study on the ancient putty from the site of the Ming Dynasty (1368–1644 CE) Baochuanchang Shipyard, Nanjing, China. (February 2019) - Gong, Yuxuan; Qiao, Chengquan; Yu, Xiang; Wang, Jun; Gong, Decai
Abstract: In 2003, the excavation of the ancient site Baochuanchang Shipyard was carried out in Nanjing, China and this shipyard was believed to have been the workshop where the huge vessels of Zheng He's fleet were built and maintained. Several pieces of ancient putty were found here, and a small piece was sampled and analyzed in this paper to study its components and structure. The results of X-ray diffraction (XRD) showed that the putty was mainly composed of calcite (CaCO3 ), while pyrolysis-gas chromatography–mass spectrometry (Py-GC–MS) analysis indicated that tung oil was used in making the putty. In addition, plant fibers inside the putty were identified as jute by the means of polarizing microscope and scanning electron microscope (SEM) analysis. These findings confirmed the putty as the so-called chu-nam putty, which was a traditional sealing material used in ancient shipbuilding. Moreover, the surface morphology of the putty was obtained by SEM, and pore size distribution was measured by gas adsorption-desorption analysis. The analytical results suggested that the putty was quite compact, which could perform well in sealing huge wooden ships. This research revealed the shipbuilding skills of the Baochuanchang Shipyard. It may provide reference for studying Zheng He's vessels and make further a contribution to the conservation and restoration of ancient wooden ships of the Ming Dynasty. Highlights: Due to a lack of historical records, the shipbuilding technologies of Zheng He's vessels especially the sealing material remains unknown. In this paper, the ancient putty excavated from the site of Baochuangchang Shipyard was analyzed. The results proved that it is the so-called chu-nam putty mainly consisted of calcite, quartz and carboxylates. Tung oil was believed to be used in making chu-nam putty, however, there is a lack of direct evidence in previous studies for proving the use of tung oil due to its rare content. In this paper, the Py-GC-MS results evidenced directly the use of tung oil in the ancient putty. The results of SEM and gas adsorption-desorption analyses indicated the putty was quite compact with relatively tiny pores. It further reflected the putty was well preserved and possessed good sealing properties.